PENGEMBANGAN KOMIK DIGITAL AUDIOVISUAL UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN TEKS NARASI SISWA KELAS V SDN KEBON BARU 07 JAKARTA - Khairunnisa, Nurraidah; Yuli Satriyani, Febrianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conduct to develop a digital audiovisual comic as a learning medium aimed at improving narrative text read comprehensions skill of fifth-grade student at SDN Kebon Baru 07. The study adopted a Research and Development (R&D) approach utilizing the ADDIE model, which consist of the analys, design, developmen, implementations, and evaluation stage. The research subject included media, material, and language experts, a classroom teacher, and 23 fifth-grade students. Data were gathered through observations, interview, expert validation sheets, questionnaires for teachers and students, and learning achievement tests. The validations result indicated that the developed product achieved feasibility scores of 96% from media experts, 98% from language experts, and 93% from material experts, all of which fell into the very valid category. The effectiveness test show a significant improvement in students’ average scores, increasing from 57.5 on the pretest to 86.5 on the posttest, with an N-Gain score of 0.74, classified as fairly effective. Furthermore, teacher and student responses reached 90% and 93%, respectively, indicating very positive perceptions. These findings suggest that the digital audiovisual comic developed in this study is both feasible and effective for use in Indonesian language learning to enhance student narrative text reading comprehension skills.